Exploring Behavioral Sleep Problems in Children With ADHD and Comorbid Autism Spectrum Disorder. Issue 10 (August 2018) - Thomas, Simone; Lycett, Kate; Papadopoulos, Nicole; Sciberras, Emma; Rinehart, Nicole
Objective: This study (a) compared behavioral sleep problems in children with comorbid ADHD and autism spectrum disorder (ASD) with those with ADHD and (b) examined child/family factors associated with sleep problems.Method: Cross-sectional study comparison of 392 children with a confirmed ADHD diagnosis (ADHD+ASD, n=93, ADHD, n=299) recruited from 21 peadiatric practises in Victoria, Australia. Data were collected from parents. Key measures included the Child Sleep Habits Questionnaire (CSHQ).Results: Children with ADHD + ASD experienced similar levels and types of behavioral sleep problems compared with those with ADHD. In both groups, the presence of co-occurring internalizing and externalizing comorbidities was associated with sleep problems. Sleep problems were also associated with parent age in the ADHD + ASD group and poorer parent mental health in the ADHD group.Conclusion: Findings suggest comorbid ASD is not associated with increased behavioral sleep problems in children with ADHD and that co-occurring internalizing and externalizing comorbidities may flag children in these groups with sleep problems.